Comparative study of understorey bird diversity of selected forest reserves in Peninsular Malaysia / Norlelah Hassan - Norlelah, Hassan (2017)
Logging activities have significantly contributed toward changes in habitat structure of many Peninsular Malaysia forests. It affected food resources and lead to reduction in diversity and abundance of forest birds. In this study, diversity, abundance and community composition of understorey birds inhabiting four forest reserves throughout Peninsular Malaysia were studied. These forest reserves are Berembun Forest Reserve, Pasir Raja Forest Reserve, Tekam Forest Reserve and Endau-Rompin Johor National Park. All forests have component of unlogged and logged forests with various regenerating levels (years of left undisturbed since last logging activity was conducted) such as 1-15 years, 16-30 years, and more than 31 years. Thirty-two field visits have been conducted to study areas from August 2009 until December 2011. Twenty mist-nets were setup for three consecutive days at each study areas to sample understorey birds. A total of 1,389 understorey birds that belong to 26 families and 112 species were captured. Berembun Forest Reserve recorded highest number of understorey bird species while Endau-Rompin Johor National Park recorded least species. Generally understorey birds in unlogged forests are more diverse than logged forests (90 species or 24 families and 75 species or 21 families respectively). Insectivorous bird, dominated by Little spiderhunter (Arachnothera longirostra) of family Nectariniidae was the most dominant species in the study area. Results indicated that higher number of individuals and species were recorded in old growth forest (> 31 years) than other forest types. Results suggested that forest disturbance and habitat degradation are the factors that caused changes in understorey bird community and species decline. Logging process also had caused reduction in environmental quality which lead to limited food resources. These have caused understorey birds to disperse to other habitats. Diversity and abundance of bird’s communities in old growth forest are recovering depending on ecological requirements of the species. The information derives from this study highlighted the effects of logging on understorey bird species and the management practice of forest reserves in Malaysia.